Student, Teacher, and School Counselor Perceptions of National School Uniforms in Malaysia - Woo, Jhia Mae; Tam, Cai Lian; Bonn, Gregory B.; Tagg, Brendon (Frontiers in Psychology, 2020)
The national school uniform remained a requirement for all primary and secondary school students in Malaysia since its first introduction by the British missionaries in the 19th century. Although it is commonly thought that wearing uniforms improve cohesion among students, little research has been done to investigate the perception of national school uniforms and perceived cohesion among Malaysian students. The aim of the current study is to explore the experiences of former students, teachers and school counsellors in relation to Malaysia’s national school uniform policy, their influence on student life, and their relationship to school and national cohesion. Three studies were conducted. In Study 1, Malaysian secondary school graduates (N=192) completed a self-report questionnaire with close and open-ended questions. In Study 2 and study 3, secondary school teachers (N=10) and school counsellors (N=6) participated in semi-structured interviews, respectively. Although students felt the uniforms were unattractive, they had neutral to somewhat positive feelings about them overall. They did not report greater school cohesion or national identity related to uniforms but did report that uniforms lessened the importance of socioeconomic and other differences. Teachers and counsellors reported similar views; they did not perceive much influence on national or school identity but did see advantages in terms of discipline and the lessening of student inequality. Generally, teachers and counsellors were in favor of school uniforms but some suggested that uniform designs could be more culturally inclusive, particularly in regard to Muslim and non-Muslim students. Limitations of using non-representative sampling and future direction for Malaysian school uniforms were discussed. This study highlights the important characteristics that should be taken into consideration by educators and policymakers for future improvement of the national school uniform policy in Malaysia.